Effect of the pruning time and application of calcium cyanamide on the dormancy breaking and productivity of cv. Niágara Branca - Maraschin, Marcelo; Koller, Otto Carlos; da Silva, Aparecido Lima (Pesquisa Agropecuaria Brasileira, 1992)
This study was carried out at the ACARESC’S TRAINING CENTER, in Florianópolis, SC, in order to evaluate the effects of pruning time and the application of calcium cyanamide (CaCN2) on the dormancy breaking in grapes (Vitis labrusca L.) cv. Niágara Branca. The treatments consisted of four pruning periods (7/3, 7/17, 7/31 and 8/18/87) followed by the painting of the pruned branches with 10% of 20% CaCN2 solutions. The number of sprouts was reduced by early pruning, but it was not affected by the treatment with CaCN2. The action of both pruning and CaCN2 treatments anticipated the bud sprouting and fruit ripening. The variables number of cluster/grapevine and total production decreased with the antecipation of pruning in more than 30 days in relation to the pruning time recommended for the region. The average weight of the clusters was not affected. No significant differences were detected on the effects of the two concentrations of calcium cyanamide.